STUDI PENANGANAN HASIL TANGKAPAN PURSE SEINE DI KM BINA MAJU KOTA SIBOLGA - Roma Yuli Felina Hutapea; Liya Tri Khikmawati; Wahyu Gusfirmansyah (Jurnal Teknologi Perikanan dan Kelautan, 2019)
Catches handling is one of the factors that affect the freshness and quality of fish catches. The effort made by the government in maintaining the quality of fishery products is by issuing KEPMEN-KP 52A/2013 concerning in Quality Assurance and Safety Requirements for Fishery Products in the Production, Processing, and Distribution Process. Government alignments by issuing KEPMEN-KP 52A/2013 are expected to produce good, safe, and healthy fishery products. The purpose of this reseacrh is to determine the activities of catches handling and determine the suitability of handling activities in KM Bina Maju with KEPMEN KP 52A/2013. The research method is a case study. The object or location of fish handling activities in KM Bina Maju that have implemented the 3C1Q Clean, Careful, Cold, and Quick principles. The suitability of handling activities in KM Bina Maju with KEPMEN KP 52A/2013, is the availability of hatch used for storage of catches that are separate from the engine room and ABK room. It's just that the hatch is not yet equipped with a sea water cooling engine and automatic air temperature control. The suitability of the workers with KEPMEN KP 52A/2013 is a condition of ABK that is healthy, does not smoke, and not spits in the storage area. The discrepancy is in the case of lack of awareness in the use of work clothes and hand washing activities before catch handling activities.